SiO2 encapsulated nanofluorophor: Photophysical properties, aggregation induced emission and its application for cell mitochondria imaging. (April 2017) - Li, Yuhao; Liu, Rui; Chang, Jin; Huang, Mingxian; Chang, Haizhou; Miao, Yuqing
Abstract: An organic fluorescent 1, 8-naphthalimide derivative (NI-1) was designed and synthesized. Its photophysical properties were systematically investigated by a series of spectroscopic and theoretical methods. The twisted intramolecular charge transfer (TICT) was proved within NI-1 in various solutions. After adding H2 O into its CH3 CN solution, the aggregation induced emission (AIE) of NI-1 occurred, during which the enhanced green-yellow fluorescence and quantum yield up to 0.62 were monitored. In addition, SiO2 was used to coat on the surface of NI-1 to fabricate the composite nano structure (NI-1@SiO2 ). This nanomaterial not only qualifies AIE-active characteristic, but also exhibits remarkable anti-photobleaching ability and good biocompatibility. The NI-1@SiO2 can go through the cell membrane and specifically light up the mitochondria. The cellular uptake mechanism studies revealed that the energy-dependent cell uptake mechanism was responsible for the NI-1@SiO2 entering cells. The NI-1@SiO2 could be utilized as an efficient AIE-active fluorescent material and mitochondria imaging reagent. Graphical abstract: Highlights: A 1, 8-naphthalimide derivative (NI-1) has been designed and synthesized. NI-1 qualifies strong AIE characteristic and can be encapsulated in SiO2 to form a nano-composite (NI-1@SiO2 ). NI-1@SiO2 can go through cell membrane and specifically light up the mitochondria. The energy-dependent cell uptake mechanism could responsible for the materials internalization.